The end of “Eskimo land”: Yupik relocation in Chukotka, 1958-1959 - Krupnik, Igor; Chlenov, Mikhail (Études/Inuit/Studies, 2007)
AbstractFifty years ago, in summer 1958, Russian authorities started a program of massive relocation of the Yupik population on the Chukchi Peninsula, Siberia. About 800 people, or roughly 70% of the small nation of 1,100 at that time, were forced to leave their home sites and were moved to other communities. Some basic facts related to the Yupik relocations of the 1950s have been known since the 1960s; but no first-hand narratives of the displaced people were ever published. The paper overviews the closing of the three largest Siberian Yupik communities of Naukan, Ungaziq (Chaplino) and Plover in 1958-1959, and the displacement of their residents as recalled from their memories and personal accounts collected by the authors during the 1970s and 1980s. The paper argues that Soviet Yupik relocations of the 1950s were unprecedented in their scale and traumatic impact, even when compared to other state-initiated resettlement programs that targeted many Inuit communities in Alaska, Canada and Greenland.